Techno-Economic Evaluation of Solar Irrigation Plants Installed in Bangladesh - Hoque, Najmul; Roy, Amit; Beg, Mohd. Rafiqul Alam; Das, B. K. (International Journal of Renewable Energy Development, 2016)
In the summer season, irrigation sector in Bangladesh suffers a lot due to the country wide electricity crisis. Solar pump offers a clean and simple alternative to the conventional fuel fired engine or grid electricity driven pump in this regard to resolve the issue. In this paper, the techno-economic analyses of solar irrigation plants installed in Bangladesh are evaluated.  It was observed that systems were running around 70% to 80% of the rated power which was quite acceptable. A 10 hp pump was able to pump 600 liter of water per minute which was also satisfactory to irrigate the land. Average operating time was found to be 8 hour/day. It was found that the overall efficiency of the systems were in between 11.39% to 16.52% whereas the typical average value of lit/Wp/year was 9200. On the other hand, the cost of irrigation to cultivate paddy in 0.161 hectares’ land for one season was 1,750 BDT by solar irrigation which was found to be lower than that of other available modes. This charge for grid electricity based irrigation was about 3,000 to 3500 BDT per 0.161 hectares’ and 2,300 to 2,600 BDT per 0.161 hectares’ for diesel engine based irrigation. According to the current financial scheme (15% equity investment, 35% credit support and remaining 50% from government through IDCOL) the average value of payback period was 5.43 years, NPV in the range from 7 to 15% and IRR was 18%. By considering 100% equity investment, however, these projects were not economically attractive. The payback period for this case was about 18 years. Study also revealed that each solar irrigation plant reduces 42.8 kg of CO2 emission per day compare to diesel engine operated pump and 2566.24 kg/day compared to grid electricity operated pump. A comprehensive effort from the Government as well as from all the stakeholders is required for further expansion of solar irrigation plants in Bangladesh. Article History: Received Sept 05, 2015; Received in revised form Dec 15, 2015; Accepted February 2, 2016; Available onlineHow to Cite This Article: Hoque, N., Roy, A., Beg, M.R.A. and Das, B.K. (2016) Techno-Economic Evaluation of Solar Irrigation Plants Installed in Bangladesh. Int. Journal of Renewable Energy Development, 5(1), 73-78.http://dx.doi.org/10.14710/ijred.5.1.73-78